Improving Education and Participation in Papua - Indriwati Mardani Bogar (Universitas Airlangga, 2026)
The development of these aspects includes the field of education. Autonomy in the development and management of education aims to make effective and efficient the management and utilization of educational resources, education equity, and improving the quality of education. This includes the establishment of education policy. Education policies are issued by local governments as support for central government policies that are tailored to the conditions of each autonomous region. The originator of the policy is none other than the solution offered by the government to the conditions or problems that occur in society. In the Strategic Plan (Renstra) prepared by the government, there are efforts to overcome educational problems, including improving the quality of education. Quality improvement covers all aspects of education, from tools to management. With optimal management of education management, it is expected that education problems can be resolved, one of which is increasing school participation.